2016
DOI: 10.1158/1535-7163.mct-15-0931
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of TLR1 I602S Polymorphism for Patients with Metastatic Colorectal Cancer Treated with FOLFIRI plus Bevacizumab

Abstract: The purpose of this study was to evaluate the clinical significance of single nucleotide polymorphisms in TLR1, TLR2, TLR6, and TAK1 in patients with metastatic colorectal cancer (mCRC). We genotyped 9 SNPs of TLR1, TLR2, TLR6, and TAK1 in mCRC patients treated with 1st-line FOLFIRI (combination therapy of irinotecan, 5-fluorouracil and folinic acid) plus bevacizumab, using a discovery cohort (TRIBE trial, n=228) and a validation cohort (FIRE-3 trial, n=297), and analyzed for the association with response rate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Here we found that LR1-N248S polymorphism was not only associated with poor survival outcome but might in uence the response to adjuvant chemotherapy. In addition to our nding, Okazaki et al also indicated that TLR1-I602S (rs5743618) could serve as a predictor of clinical response to FOLFIRI plus bevacizumab in patients with mCRC [41]. Moreover, Deng et al showed that TLR1/2 expression had a positive correlation with lung cancer patients' survival [42], suggesting TLR1/2 signaling may in uence the therapeutic response to chemotherapy by modulating antitumor immunity.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Here we found that LR1-N248S polymorphism was not only associated with poor survival outcome but might in uence the response to adjuvant chemotherapy. In addition to our nding, Okazaki et al also indicated that TLR1-I602S (rs5743618) could serve as a predictor of clinical response to FOLFIRI plus bevacizumab in patients with mCRC [41]. Moreover, Deng et al showed that TLR1/2 expression had a positive correlation with lung cancer patients' survival [42], suggesting TLR1/2 signaling may in uence the therapeutic response to chemotherapy by modulating antitumor immunity.…”
Section: Discussionsupporting
confidence: 68%
“…OXP can trigger immunogenic cell death (ICD) through the release of high mobility group box 1 (HMGB1) to promote DC maturation via TLR2 or TLR4, and induce antitumor immunity [32,39]. TLR1 forms a heterodimer with TLR2, were suggested to be essential in regulating mucosal immune response within the gut [40] and the polymorphism of TLR1 is associated with the response to FOLFIRI plus bevacizumab in metastatic CRC [41]. Therefore, we assumed that TLR1-N248S polymorphism may attenuate the HMGB1-activated TLR2 signaling for DC maturation by immunogenic chemotherapeutic agent OXP to in uence the therapeutic e cacy.…”
Section: Defective Tlr1 Signaling Attenuated Oxp-elicited Tlr2 Activa...mentioning
confidence: 99%
“…In the discovery arm, patients with the TLR-1-rs5743618-TT genotype had shorter PFS and OS compared with GT/TT genotypes (HR:1.50, p = 0.046; HR:1.53, p = 0.025, respectively). In the same group, patients with the TAK1-rs1145727-AA genotype had a shorter OS than patients with GA/GG genotypes (23 vs. 26.8 months, p = 0.008) [47]. The TLR-1-rs5743618 polymorphism is a missense (Ser602Ile) variation in which the presence of the mutant G allele is associated with a decrease in IL-6 and TNF-α levels and therefore with a reduction in TLR-1-mediated immunity [130].…”
Section: Toll-like Receptors (Tlrs)mentioning
confidence: 88%
“…In patients with metastatic colorectal cancer (mCRC), TLR1 rs5743618 SNP was associated with a significant response to FOLFIRI plus bevacizumab chemotherapy. Based on these findings, TLR1 rs5743618 might be a predictive biomarker for the advantage of FOLFIRI plus bevacizumab response in mCRC patients [35]. According to Castano-Rodriguez and colleagues' review, rs5743618 polymorphism has also been associated with decreased risk of gastric cancer among the German population (OR < 1) [36].…”
Section: Tlr Polymorphisms and Their Role In Cancer Developmentmentioning
confidence: 99%